Identification of a novel TECRL variant causing type 3 catecholaminergic polymorphic ventricular tachycardia - Chen, Yun; Shen, Jie; Chen, Long; Sun, Ling (Frontiers in Pediatrics, 2025)
BackgroundCatecholaminergic polymorphic ventricular tachycardia (CPVT) is a leading cause of sudden cardiac death (SCD) in young patients, characterized by bidirectional or polymorphic ventricular tachycardia often induced by physical exertion or emotional stress.ResultsWe analyzed a 12-year-old girl with CPVT who suffered cardiac and respiratory arrest. Clinical data were derived from medical records. Whole-exome sequencing (WES) and Sanger sequencing identified two missense mutations in the trans-2,3-enoyl-CoA reductase-like (TECRL) gene (NM_001010874.5: c.587G > A p.Arg196Gln and NM_001010874.5: c.868C > T p.Pro290Ser), potentially pathogenic and associated with type 3 CPVT (CPVT3). Functional studies suggested both mutations could lead to reduced protein expression. We also discovered a novel TECRL mutation (NM_001010874.5: c.868C > T p.Pro290Ser). This study further supports the role of TECRL as one cause of CPVT.ConclusionsIn this study, functional studies implicate these variants as the cause of CPVT in this patient.